Digital strategizing: An assessing review, definition, and research agenda - Morton, Josh; Amrollahi, Alireza; Wilson, Alexander D. (The journal of strategic information systems, 2022)
•Explores a nexus between information systems and strategy practice.•Provides an in-depth assessing review of 71 selected papers at this nexus.•Illustrates how the nexus represents a research domain which we call ‘digital strategizing’.•Proposes a definition for digital strategizing.•Presents a research agenda for continued theorisation of digital strategizing. This paper provides an assessing review and agenda for research at the ‘nexus’ between information systems and strategy practice. The review aims to understand the nature of this connection between the two areas, where information systems scholars strive to understand the everyday work of practitioners in organisations and the impact of digital technologies in strategizing, whilst strategy practice scholars seek a greater understanding of such technologies and their use by strategists. Despite a developing body of work relevant to both information systems and strategy practice, and several editorials calling for ‘synergy’, we still collectively know little about the state of knowledge at the nexus. To address this, our review identifies several constructs that provide linkages between information systems and strategy practice to reveal more about the current state of knowledge and to develop a formal definition for a domain which we call digital strategizing. We conclude by outlining an agenda to encourage and accelerate future research on digital strategizing.